2013
DOI: 10.1063/1.4812975
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent strain localization and texture evolution of highly nanotwinned Cu

Abstract: Strong differences in the plastic strain and texture development in high purity nanotwinned copper foils deformed to failure in tension at ambient and liquid nitrogen (LN) temperatures have been observed. High energy microdiffraction patterns for the room temperature (RT) sample showed two distinct deformation regions relative to its fracture surface: d < 500 μm and d > 500 μm; while for the sample deformed at 77 K, three distinct regions were observed: d < 120 μm, 120 μm < d &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The inclusion of TBs in the film microstructure for low-intermediate SFE metals has shown a direct impact on the properties of the material, where the mechanical, thermal, and chemical properties are enhanced [1][2][3][4][5][6][7][8]. These improved properties have increased the working space of nanotwinned (nt) metals and contribute to the development of fundamental research for material's behavior at the nanoscale, particularly in low SFE metals with high TBs density [2,5,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of TBs in the film microstructure for low-intermediate SFE metals has shown a direct impact on the properties of the material, where the mechanical, thermal, and chemical properties are enhanced [1][2][3][4][5][6][7][8]. These improved properties have increased the working space of nanotwinned (nt) metals and contribute to the development of fundamental research for material's behavior at the nanoscale, particularly in low SFE metals with high TBs density [2,5,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of nt materials has been highlighted in the mechanical testing of nanotwinned Cu, which showed high strength and good ductility compared to UFG or coarse grain Cu [4,6,7]. Additionally, nt materials have shown good corrosion resistance, thermal stability, and tolerance to radiation damage [8][9][10]. To date, nt materials have been synthesized using different metals and alloys systems, such as Cu, Ag, Cu-Al, Cu-Zn, and stainless steel among others [4,6,7,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [15] showed that coherent NTs in the UFG Cu led to a noticeable improvement in damage tolerance. Furnish et al [16] observed plastic strain and texture development in NT Cu foils in tension and found two distinct deformation regions relative to fracture surface. These experimental observations have greatly contributed to our current understanding, but experimental investigation alone is not sufficient to provide a complete picture of the underlying mechanisms that control the overall strength and ductility.…”
Section: Introductionmentioning
confidence: 99%